Kepemimpinan Transformasional Kepala Madrasah dalam Meningkatkan Kualitas Pendidikan - Eko Saifudin; Imam Satibi; Benny Kurniawan; Eliyanto Eliyanto (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2024)
The essence of transformation is changing potential into real energy. Madrasah heads who are able to carry out leadership transformations mean they can turn their institutions into energy to improve the quality of educational processes and output. The aims of this research are (1) to describe and analyze the transformational leadership of madrasa heads at MTs Ma'arif NU 1 Sumpiuh Banyumas, and (2) to describe and analyze the leadership of madrasa heads in improving the quality of education through transformational leadership at MTs Ma'arif NU 1 Sumpiuh Banyumas. This research is qualitative research using pedagogical, management and theological approaches. The primary data was obtained from the madrasa head, teachers, administrative staff, and related parties in the madrasa as well as the community who have been helping the madrasa in community development, while the secondary data was obtained from books, the internet, and other sources deemed relevant to the problems studied. Data was collected through observation techniques, interviews and documentation studies. This research found that the leadership of the head of MTs Ma'arif 1 NU Sumpiuh Banyumas in carrying out the main tasks is a democratic leader, indications of which can be seen from the description of the main tasks, strategies, actions and active, dynamic and directed madrasah programs that try to utilize every people for the benefit of the progress and development of the madrasah. The transformational leadership of madrassa heads has had a positive impact on improving the quality of education, although there are still several weaknesses that need to be corrected and require better strategies from madrasah heads in carrying out their main duties, especially in overcoming the problem of the community's lack of interest in sending their children to MTs Ma'arif NU 1 Sumpiuh Banyumas. The final implication of this research is the importance of the madrasa head as a leader to always carry out his main duties optimally in order to improve the quality of education in the madrasa. For this purpose, madrasah heads must be able to mobilize madrasah resources, in relation to planning and evaluating madrasah programs, curriculum development, learning, personnel management, learning facilities and resources, finance, student services, madrasah with the community and creating a madrasah climate